Does Managed Care Improve Access to Care for Medicaid Beneficiaries with Disabilities? A National Study - Teresa A. Coughlin; Sharon K. Long; John A. Graves (SAGE Publishing, 2008)
States increasingly are shifting Medicaid beneficiaries with disabilities from the fee-for-service (FFS) delivery system to managed care in an effort to control program costs and address long-standing problems with access to care under the program. Using a county-based measure of managed care enrollment and pooled data from the 1997 to 2004 National Health Interview Surveys, we investigate whether Medicaid managed care (MMC), relative to FFS Medicaid, improves access to care. We find some evidence of improved access to care under MMC; however, the gains appear to be largely limited to beneficiaries in urban areas with fully capitated managed care. There is little evidence of improved access under primary care case management or, regardless of MMC type, in rural areas.